Effects of using recycled paper in inkjet printing system on colour difference - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose This study aims to examine the colour changes affecting inkjet prints after the recycling of papers. Design/methodology/approach For recycling, papers prepared with the INGEDE 11p standard are recycled four times. Pulping, storage, flotation, beating and bleaching processes are applied for each recycling, respectively. Inkjet prints are made on the obtained test papers, and colour measurements are made using an X-Rite eXact spectrophotometer according to the ISO 13655:2017 standard. These processes are applied again to the papers which are recycled four times, and the results are analyzed. In addition, the values of Delta E-00 ', Delta L ', Delta H ' and Delta C ' are calculated according to ISO 11664-6:2014 standard by making some calculations according to obtained the L ' a ' b ' values. Findings It is determined that the Delta E-00 value increases after each recycling in cyan magenta and yellow colour, whereas it decreases in black. The highest Delta E-00 value is calculated after the fourth recycling stage is yellow with a value of 8.33. The lowest Delta E-00 value detected is black with a value of 0.76 after the fourth recycling stage. This paper observes that the colour with the most variation in hue angle among recycling repetitions is black and the colour with the highest hue angle value is yellow. It is seen that repeating recycling causes increase in the chromatic values of the prints. Originality/value After the fourth recycling stage, colour changes have reached an important point and can cause important printing problems. In this case, the customer's approval must be obtained to continue printing. This case is valid for Delta E-00 values. Colour differences for print contrast, trapping and print chroma values are either not very important or are positive for quality.
Keywords: CIEDE 2000; Delta E-00; Chroma; Trapping; Recycling; Gloss 60 degrees; PRINTABILITY; PAPERBOARDS